The REPO handbook - Choudhry, Moorad (Oxford ; Boston : Butterworth-Heinemann, 2010)
The book presents an overview of repo vehicles and markets with sufficient depth for those seeking detailed explanations. In three parts it demonstrates how these secured loans fit into global capital markets and why they account for up to 50% of daily settlement activity in non-US government bonds worldwide.
Includes bibliographical references and index.
rua 30/04/13
Loans
Keywords: Repurchase agreements; Repo